Delftse foundations of computation - Hugtenburg, Stefan; Yorke-Smith, Neil; Technische Universiteit Delft; BC Open Textbook Project; BCcampus (Delft University of Technology, 2019)
"Delftse Foundations of Computation is a textbook for an introductory course in theoretical computer science. It includes topics from propositional and predicate logic, proof techniques, set theory and the theory of computation, along with practical applications to computer science. It has no prerequisites other than a general familiarity with computer programming"--BCcampus website.
1. Introduction -- 2. Logic. Propositional logic ; Boolean algebra ; Application: logic circuits ; Predicate logic ; Deduction -- 3. Proof. A little historical background ; Mathematical proof ; Proof by contradiction ; Mathematical induction ; Strong mathematical induction ; Application: recursion and induction ; Recursive definitions ; Invariants -- 4. Sets, Functions, and Relations. Basic concepts ; The Boolean algebra of sets ; Application: Programming with sets ; Functions ; Application: programming with functions ; Counting past infinity ; Relations ; Application: relational databases -- 5. Looking Beyond.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references (page 157) and index.
Description based on online resource; title from pdf title page (viewed March 4, 2020).
Keywords: Computer science; Electronic books